2006
DOI: 10.1083/jcb.200509096
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and activation of Rac1 are mediated by the exchange factor β-Pix

Abstract: Rho guanosine triphosphatases (GTPases) are critical regulators of cytoskeletal dynamics and control complex functions such as cell adhesion, spreading, migration, and cell division. It is generally accepted that localized GTPase activation is required for the proper initiation of downstream signaling events, although the molecular mechanisms that control targeting of Rho GTPases are unknown. In this study, we show that the Rho GTPase Rac1, via a proline stretch in its COOH terminus, binds directly to the SH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
236
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(252 citation statements)
references
References 52 publications
16
236
0
Order By: Relevance
“…b-PIX (also known as ARHGEF7) is a RhoGEF involved in various small GTPase signaling pathways. 30 b-PIX contains a PDZ-binding motif at its C-terminal end. We recently demonstrated that EBP50 interacts with b-PIX through its first PDZ domain, and b-PIX associates with the podocalyxin-EBP50-ezrin complex.…”
Section: Resultsmentioning
confidence: 99%
“…b-PIX (also known as ARHGEF7) is a RhoGEF involved in various small GTPase signaling pathways. 30 b-PIX contains a PDZ-binding motif at its C-terminal end. We recently demonstrated that EBP50 interacts with b-PIX through its first PDZ domain, and b-PIX associates with the podocalyxin-EBP50-ezrin complex.…”
Section: Resultsmentioning
confidence: 99%
“…localization of the Rac1 GEF, ␤-PIX. It was recently reported that the interaction with ␤-PIX was necessary and sufficient for Rac1 recruitment to membrane ruffles and to focal adhesions (ten Klooster et al, 2006). We therefore hypothesized that the depletion of ARF6 might allow the relocalization of ␤-PIX to the plasma membrane and the activation of Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…The Rac1 Guanine-Nucleotide Exchange Factor ␤-PIX Is Relocalized to the Plasma Membrane in ARF6-depleted Cells It is generally accepted that relocalization of small GTPases is necessary for their activation, although the mechanisms that control targeting of Rho GTPases in general are poorly understood. It was recently demonstrated that Rac1 binds directly to ␤-PIX (p21-activated kinases [PAK]-interacting exchange factor) and that this interaction is necessary and sufficient for Rac1 recruitment to membrane ruffles, providing a model for the intracellular targeting and localized activation of Rac1 (ten Klooster et al, 2006). To begin to address why Rac1 is found basally activated in ARF6-depleted cells, we examined the localization of the Rac/Cdc42 GEF ␤-PIX.…”
Section: Remodelling Of the Actin Cytoskeleton Induced By Arf6 Depletmentioning
confidence: 99%
“…In addition to their potential enzymatic activity on Rho and Arf GTPases, PIX and GIT proteins are essential to the recruitment of signaling complexes including Rac1 and PAK1. They also integrate signals from Src and FAK to regulate focal adhesion dynamics (Brown et al, 2005;ten Klooster et al, 2006). The multimolecular complex PIX-GIT-PAK may thus be important for regulating Rho GTPases and podosome organization in osteoclast.…”
Section: Exchange Factors and Osteoclast Biologymentioning
confidence: 99%